Manfaat Komunikasi Guru dalam Memberikan Motivasi Belajar Kepada Siswa di MTs - Nasri, Nasri (YASIN, 2022)
Communication is the process of delivering or receiving messages from one person to another, either directly or indirectly, in writing, verbally or in nonverbal language. Teachers' communication skills in learning activities include 4 main abilities, namely: First, the ability of teachers to develop positive attitudes in learning activities. This ability consists of: (1) Recognizing the strengths and weaknesses of students in learning activities. (2) Helping students to develop self-confidence in learning activities. (3) Help clarify thoughts and feelings so that others can understand and exchange ideas in learning activities. Learning motivation comes from the Latin word "movere" which means "encouraging or moving". "Motivation is something that encourages individuals to behave which directly causes the emergence of behavior. A person will do an action no matter how hard it is if he has high motivation. Likewise, in learning motivation plays a large enough role in achieving results. Another opinion suggests that motivation is the basic drive that moves a person to behave. This drive resides in a person who moves him to do something according to his inner urge.